Media Markets and Localism: Does Local News en Español Boost Hispanic Voter Turnout? - Oberholzer-Gee, Felix; Waldfogel, Joel (American Economic Review, 2009)
In the past decade Americans have increasingly turned their attention to nonlocal information sources, raising concerns about disengagement from local communities. Regulation sometimes seeks to curtail the integration of media markets through the promotion of “localism.” This paper examines the role of local media. We make use of the rapid growth of Hispanic communities in the United States to test whether the presence of local television news affects local civic behavior. We find that Hispanic voter turnout increased by 5 to 10 percentage points, relative to non-Hispanic turnout, in markets where Spanish-language local television news became available. (JEL D72, J15, L82)